Assessment of Dietary Intake and Eating Attitudes in Recreational and Competitive Adolescent Rock Climbers: A Pilot Study - Michael, Marisa K.; Joubert, Lanae; Witard, Oliver C. (Frontiers in Nutrition, 2019)
The dietary intake patterns and eating attitudes of adolescent climbers has not been studied. To fill this gap, we administered three surveys to 22 rock climbers (13 males, 9 females, age 14.21.9 years): climbing ability, three-day dietary recall, and Eating Attitude Test-26 (EAT-26). The majority (82%) of climbers did not meet their target energy intake (target = 2471493 kcalday-1; actual = 1963 581 kcalday-1) (p=0.003) and 86% of climbers consumed below their target carbohydrate intake (target = 28367 gday-1; actual intake = 22672 gday-1) (p=0.009). Average dietary protein intake was 95  51 gday-1, with the majority of climbers meeting their target intake of 8821 g (p=0.580). Seventy-three percent of climbers consumed below their target dietary fat intake (target = 9021 gday-1; actual = 6920 gday-1) (p=0.001). Average EAT-26 scores were 5.3± 4.1, indicating minimal risk of disordered eating attitudes/behaviors. There were no significant differences in boulderers vs. top rope climbers for energy/macronutrient intake, BMI, and EAT-26 score. There were no associations between energy intake and EAT-26 score (R2= 0.245, p=0.271) or climbing ability and EAT-26 score (R2=, p=0.217). These data suggest that adolescent climbers fail to meet target dietary intakes except protein, and exhibit minimal risk of disordered eating.